Thermoelectric performance of the 2D Bi₂Si₂Te₆ semiconductor - Luo, Yubo (2022)
Bi2Si2Te6, a 2D compound, is a direct band gap semiconductor with an optical band gap of 0.25 eV, and is a promising thermoelec-tric material. Single-phase Bi2Si2Te6 is prepared by a scalable ball-milling and annealing process and the highly densified polycrys-talline samples are prepared by spark plasma sintering. Bi2Si2Te6 shows a p-type semiconductor transport behavior and exhibits an intrinsically low lattice thermal conductivity of ~0.48 Wm-1K-1 (cross-plane) at 573 K. The first-principles density functional theory calculations indicate that such low lattice thermal conductivity is derived from the interactions between acoustic phonons and low-lying optical phonons, local vibrations of Bi, the low Debye temperature and strong anharmonicity result from the unique 2D crystal structure and metavalent bonding of Bi2Si2Te6. The Bi2Si2Te6 exhibits an optimal figure of merit ZT of ~0.51 at 623 K, which can be further enhanced by the substitution of Bi with Pb. Pb doping leads to a large increase in power factor S2σ, from ~4.0 μWcm-1K-2 of Bi2Si2Te6 to ~8.0 μWcm-1K-2 of Bi1.98Pb0.02Si2Te6 at 775 K, owing to the increase in carrier concentration. Moreover, Pb doping in-duces a further reduction in the lattice thermal conductivity to ~0.38 Wm-1K-1 (cross-plane) at 623 K in Bi1.98Pb0.02Si2Te6, due to strengthened point defect (PbBi’) scattering. The simultaneous optimization of the power factor and lattice thermal conductivity achieves a peak ZT of ~0.90 at 723 K and a high average ZT of ~0.66 at 400–773 K in Bi1.98Pb0.02Si2Te6.